The Effectiveness of Cooperative Financial Management on the Economic Empowerment of Rural Communities in Bogor Regency: Efektivitas Pengelolaan Keuangan Koperasi terhadap Pemberdayaan Ekonomi Masyarakat Desa di Kabupaten Bogor - Rahwana, Rudy; Rahman, Ali (UNIB Press, 2025)
This study aims to analyze the effectiveness of financial management in cooperatives in supporting economic empowerment of rural communities in Bogor Regency. The research uses a quantitative approach with descriptive analysis techniques. Data were collected through interviews and questionnaires distributed to cooperative members and managers in several villages. The results show that good financial management in cooperatives can enhance economic empowerment by improving access to capital, training, and business development. However, there are challenges in effective financial management, such as a lack of transparency and inadequate professionalism in management. Based on these findings, it is recommended that cooperatives in Bogor Regency pay more attention to transparency and professionalism in financial management to improve the economic empowerment of rural communities.